2018
DOI: 10.1016/j.jde.2018.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Global existence and stabilization in a degenerate chemotaxis-Stokes system with mildly strong diffusion enhancement

Abstract: A class of chemotaxis-Stokes systems generalizing the prototypeis considered in bounded convex three-dimensional domains, where φ ∈ W 2,∞ (Ω) is given.The paper develops an analytical approach which consists in a combination of energy-based arguments and maximal Sobolev regularity theory, and which allows for the construction of global bounded weak solutions to an associated initial-boundary value problem under the assumption that m > 9 8 .(0.1) Moreover, the obtained solutions are shown to approach the spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(33 citation statements)
references
References 43 publications
(70 reference statements)
0
33
0
Order By: Relevance
“…It has also been observed that when S = S(x, ρ, c) is a tensor, the corresponding chemotaxis-fluid system loses some energylike structure, which plays a key role in the analysis of the scalar-valued case. Despite these challenges, some comprehensive results on the global-boundedness and large time behavior of solutions are available in the literature (see [3,19,20,25,27,29,33,34,35] for example). It has been shown that when S = S(x, ρ, c) is a tensor fulfilling |S(x, ρ, c)| ≤ C S (1 + ρ) α for some α > 0 and C S > 0, (1.4) the three-dimensional system (1.3) with µ = 0, κ = 0 admits globally bounded weak solutions for α > 1/2 [27], which is slightly stronger than the corresponding subcritical assumption α > 1/3 for the fluid-free system.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been observed that when S = S(x, ρ, c) is a tensor, the corresponding chemotaxis-fluid system loses some energylike structure, which plays a key role in the analysis of the scalar-valued case. Despite these challenges, some comprehensive results on the global-boundedness and large time behavior of solutions are available in the literature (see [3,19,20,25,27,29,33,34,35] for example). It has been shown that when S = S(x, ρ, c) is a tensor fulfilling |S(x, ρ, c)| ≤ C S (1 + ρ) α for some α > 0 and C S > 0, (1.4) the three-dimensional system (1.3) with µ = 0, κ = 0 admits globally bounded weak solutions for α > 1/2 [27], which is slightly stronger than the corresponding subcritical assumption α > 1/3 for the fluid-free system.…”
Section: Introductionmentioning
confidence: 99%
“…When m = 1 in (1), namely, the diffusion of bacteria cell are assumed to be random, Tao and Winkler [29] proved that this model admits a global weak solution, and a more interesting fact is that, the weak solution will become smooth after some time. Recently, chemotaxis models featuring a density-dependent diffusion term have drawn great attention from many authors [7,1,28,35,38,18,34]. For this system with the porous medium diffusion (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The first effort to this 3-D problem is due to the work by Di Francesco et al [3], in which, they obtained the existence of global bounded weak solutions for m in some finite interval, namely m ∈ 7+ √ 217 12 , 2 (approximating to (1.8109, 2]); It was Tao and Winkler [21], in 2013, who established the global existence of locally bounded weak solutions with m belonging to the infinite interval ( 8 7 , +∞). Afterwards, Winkler [24] supplemented the uniform boundedness of solutions for the case m > 7 6 ; Recently, Winkler [25] further improved this result to the case m > 9 8 with Ω being a convex domain. However, as mentioned by Winkler [25], the question of identifying an optimal condition on m ≥ 1 ensuring global boundedness in the three-dimensional version of (1.3) remains an open challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Afterwards, Winkler [24] supplemented the uniform boundedness of solutions for the case m > 7 6 ; Recently, Winkler [25] further improved this result to the case m > 9 8 with Ω being a convex domain. However, as mentioned by Winkler [25], the question of identifying an optimal condition on m ≥ 1 ensuring global boundedness in the three-dimensional version of (1.3) remains an open challenge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation